Syndetic Coordination Analysis in Compound Sentence. Case Study: The Bucket List Story - Novi Krismayanti, Novi; Maharani, Putu Devi; Tustiawati, Ida Ayu Mela (Journal of Language and Applied Linguistics, 2024)
Compound sentence has two or more independent clauses and join together by coordinating conjunction. The aims of this study are to find out syndetic coordination in compound sentence and the constituent structure of compound sentence. The data were taken from The Bucket List Story on Wattpad by Neve Adams. This study used qualitative method to analyze the data and used theory proposed by Quirk and Greenbaum(1973) to identify the coordination in compound sentence and used the theory purposed by Brown and Miller (1991) to analyze the constituent structure by using tree diagram. Observation and note taking were used to collect the data. In collecting the data, the researcher used several steps, such as reading the story intensively, taking note and rewriting the data that contained of compound sentence and the last steps and classifying the data based on the types of compound sentence found in the data. Hence, the results of this study shows there are 78 or 100% data involved as syndetic coordination. There are 56 or 71,80% used coordinator and, 14 or 17,95% used coordinator but, 1 data or 1,28% used coordinator or and 7 data or 8,97% used coordinator so. The coordinator and is mostly found in the data with 56 data or 71,80%, then the coordinator for, nor, yet did not find in the data.